SOLUTION OF NEWTONIAN FLUID FLOW PROBLEM IN TWO DIMENSIONS SOLVED BY SIMPLE ALGORITHEM - Hussein, Mohammed; Abdul Hadi, Ahmed (Iraqi Journal of Science, 2024)
In this paper, a consideration is given to viscose, incompressible and Newtonian fluid flowing in a pipe with square cross-section under the action of pressure gradient. In particular consideration is given to first order fluid flow which can be represented by the equation of state of the form:Tij = 2η eij , i,j = 1,2Where η is constant of fluid, Tij and eij are the stress and rate of strain respectively. Cartesian coordinate has been used to describe the fluid motion and it found that motion equations are controlled by Reynolds number. The motion equations are solved by a semi-implicit algorithm namely Semi-Implicit Method for Pressure Linked Equations (SIMPLE).